Women farmers in Central America : myths, roles, reality. - YUDELMAN, Sally W. (1994)
Argues that women farmers have been rendered invisible by the widely held belief that women do not work in agriculture, or do so only temporarily for reasons of poverty. Identifies barriers to opportunity as (1) lack of access to land, (2) public policy, which generally exclude all but the large- and some of the medium-sized producers, (3) in general, women are not integrated into main-stream, public sector agricultural or natural resource programs.